New N, N-dimethylcarbamate inhibitors of acetylcholinesterase: design synthesis and biological evaluation. (4th November 2016) - De Vita, Daniela; Pandolfi, Fabiana; Ornano, Luigi; Feroci, Marta; Chiarotto, Isabella; Sileno, Ilaria; Pepi, Federico; Costi, Roberta; Di Santo, Roberto; Scipione, Luigi
Abstract: A series of N, N- dimethylcarbamates containing a N, N -dibenzylamino moiety was synthesized and tested to evaluate their ability to inhibit Acetylcholinesterase (AChE). The most active compounds4 and8, showed 85 and 69% of inhibition at 50 μM, respectively. Furthermore, some basic SAR rules were outlined: an alkyl linker of six methylene units is the best spacer between the carbamoyl and dibenzylamino moieties; electron-withdrawal substituents on aromatics rings of the dibenzylamino group reduce the inhibitory power. Compound4 produces a slow onset inhibition of AChE and this is not due to the carbamoylation of the enzyme, as demonstrated by the time-dependent inhibition assay of AChE with compound4 and by MALDI-TOF MS analysis of trypsinized AChE inhibited by compound4 . Instead, compound4 could act as a slow-binding inhibitor of AChE, probably because of its high conformational freedom due to the linear alkyl chain.